ATP and NAD+ Deficiency in Parkinson’s Disease - Mischley, Laurie K.; Shankland, Eric; Liu, Sophia Z.; Bhayana, Saakshi; Fox, Devon J.; Marcinek, David J. (Nutrients, 2023)
The goal of this study is to identify a signature of bioenergetic and functional markers in the muscles of individuals with Parkinson’s disease (PD). Quantitative physiological properties of in vivo hand muscle (FDI, first dorsal interosseus) and leg muscle (TA, Tibialis Anterior) of older individuals with PD were compared to historical age/gender-matched controls (N = 30). Magnetic resonance spectroscopy and imaging (MRS) were used to assess in vivo mitochondrial and cell energetic dysfunction, including maximum mitochondrial ATP production (ATPmax), NAD concentrations linked to energy/stress pathways, and muscle size. Muscle function was measured via a single muscle fatigue test. TA ATPmax and NAD levels were significantly lower in the PD cohort compared to controls (ATPmax: 0.66 mM/s ± 0.03 vs. 0.76 ± 0.02; NAD: 0.75 mM ± 0.05 vs. 0.91 ± 0.04). Muscle endurance and specific force were also lower in both hand and leg muscles in the PD subjects. Exploratory analyses of mitochondrial markers and individual symptoms suggested that higher ATPmax was associated with a greater sense of motivation and engagement and less REM sleep behavior disorder (RBD). ATPmax was not associated with clinical severity or individual symptom(s), years since diagnosis, or quality of life. Results from this pilot study contribute to a growing body of evidence that PD is not a brain disease, but a systemic metabolic syndrome with disrupted cellular energetics and function in peripheral tissues. The significant impairment of both mitochondrial ATP production and resting metabolite levels in the TA muscles of the PD patients suggests that skeletal muscle mitochondrial function may be an important tool for mechanistic understanding and clinical application in PD patients. This study looked at individuals with mid-stage PD; future research should evaluate whether the observed metabolic perturbations in muscle dysfunction occur in the early stages of the disease and whether they have value as theragnostic biomarkers.